Clostridioides difficile Infections in Adult and Pediatric Intestinal and Multivisceral Transplant Patients: The Experience of a Single, Tertiary-Care Transplant Center From 2009 to 2018. Issue 3 (May 2020) - Modi, Anita; Gonzalez, Blanca E.; Brizendine, Kyle D.
Abstract : Background: Solid organ transplant (SOT) recipients are at increased risk of Clostridioides difficile infection (CDI). Studies addressing the epidemiology of CDI in intestinal and multivisceral transplant are limited. Since 2013, our center greatly expanded its intestinal and multivisceral transplant program, providing the consummate opportunity to examine CDI in this vulnerable population. Methods: We conducted a retrospective study of all intestinal and multivisceral transplant recipients between 2009 and 2018. Results: We identified 86 patients who underwent a total of 94 transplants. There were 60 isolated intestinal transplants (64%), 21 intestine/pancreas/liver (22%), 10 intestine/pancreas (11%), 2 intestine/pancreas/liver/kidney (2%), and 1 intestine/kidney transplant (1%). All but 3 patients received perioperative metronidazole. Four patients (5%) had CDI before transplant, but none experienced recurrence in the first 6 months posttransplant. Five patients suffered 7 mild-moderate episodes of early CDI (attack rate, 5.9%). Three patients (60%) with early CDI developed rejection, similar to the observed incidence (70%) in patients without CDI. Two patients with early CDI developed recurrent infection; both of these patients underwent intestinal retransplant. Overall, 1-year mortality was similar (20% among patients with early CDI vs. 23% among those without early CDI). Conclusions: For certain solid organ transplant recipients, an association between CDI and allograft loss, rejection, and mortality has been shown. Although limited by sample size, we observed that early CDI was not associated with those outcomes in the present investigation. Multicenter studies are merited to explore risk factors for CDI and associations with transplant-related outcomes in intestinal and multivisceral transplant recipients. Abstract : Solid organ transplant (SOT) recipients are at increased risk of Clostridioides difficile infection (CDI). For certain SOT recipients, an association between CDI and allograft loss, rejection, and mortality has been shown. Although limited by sample size, the authors observed that early CDI was not associated with those outcomes in their single-center investigation. Multicenter studies are merited to explore risk factors for CDI and associations with transplant-related outcomes in intestinal and multivisceral transplant recipients.